EFFICIENCY OF LANSOPRAZOLE IN THE TREATMENT OF CHRONIC GASTRODUODENITIS IN CHILDREN - Rustamov Мардонкул (International Journal of Scientific Pediatrics, 2025)
Abstract. The original article presents the results of dynamic studies of the clinical picture after the use of a new drug lasoprazole in children with chronic gastroduodenitis. The results of the study are recommended for widespread implementation in the practice of general practitioners, primary health care clinics. Objective: To evaluate the effectiveness of lansoprazole in comparison with standard therapy with omeprazole in the treatment of chronic gastroduodenitis in children. Materials and methods: A comparative study of 60 children with chronic gastroduodenitis was conducted, divided into two groups of 30 people. The first group received lansoprazole, the second group - omeprazole as part of complex therapy. Efficiency was assessed using general clinical, laboratory and instrumental diagnostic methods. Results: The use of lansoprazole demonstrated a statistically significant improvement in clinical indicators and faster pain relief compared to the omeprazole group. Conclusions: Lansoprazole is an effective drug for the treatment of chronic gastroduodenitis in children and can be considered as an alternative to omeprazole.